Monitoring banking sector risks: An applied approach - Christian Weistroffer; Veronica Vallés (Deutsche Bank Research, 2008)
Despite abundant empirical evidence on the merits and limits of early-warning systems for banking crises the day-to-day use of such systems seems to be limited. Reluctance to use such systems may partly be explained by the difficulties to operationalise the proposed models, which are often demanding in terms of data requirements and/ or methodologies. We try to overcome these difficulties and show how an early-warning system can be implemented in practice. Drawing on existing empirical work, we develop a model that provides timely and readily digestible information on macroeconomic developments, e.g. booming credit volumes, excessively rising asset prices or exchange rates, which in the past typically preceded banking crises. Our model is tailored to meet the professional needs of an internationally operating private sector financial institution and can be applied across a wide range of industrial countries and emerging markets.
Keywords: E44; F37; G21; 330; banking crisis; early-warning system; credit risk management; Bankrisiko; Bankenkrise; Frühwarnsystem; Kreditrisiko; Risikomanagement